Meal planning as a strategy to support healthy eating - Fernandez, Melissa; Desroches, Sophie; Marquis, Marie; Provencher, Véronique (Nutrition Science en évolution)

(untitled) (Ordre professionnel des diététistes du Québec, 2020)
Meal planning is cited in the latest version of Canada’s Dietary Guidelines as one of four important food skills that help individuals choose, purchase and prepare healthy snacks and foods on a regular basis for themselves and members of their household. While meal planning is often mentioned as a strategy to overcome the main barrier to healthy eating, lack of time, it may also assist individuals reduce stress related to mealtimes and increase frequency of family meals. Although, there is relatively sparse literature that meal planning confers benefits to the diet, there is a history of evidence indicating that it helps manage dietary restrictions related to specific diseases (e.g., diabetes), which can translate into helping the general public consume more fruits and vegetables, while consuming fewer processed foods. In 2013 Health Canada implemented a one-year communication campaign to promote meal planning to Canadian parents as a strategy to increase home-based food preparation and family meals. The campaign evaluation found that awareness was associated with greater odds of having more positive attitudes towards meal planning. However, more than half of parents also reported that lack of time was a major barrier for meal planning. Dietitians can recommend meal planning as a viable strategy to help the public and patients overcome barriers to healthy eating. However, they will likely also need to provide guidance through education and tools to overcome barriers related to meal planning.